1996
DOI: 10.1002/cvde.19960020207
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of the production of C60 thin films by PECVD, combustion, or pyrolysis

Abstract: A short review of CW production methods is first presented with an emphasis on thin tilms for electronic applications. These films are currently made by first producing the fullerene, purifying it and then depositing by different evaporation techniques. Results of an unsuccessful attempt to produce these tilms by PECVD from organic precursors (cyclopentadiene and naphthalene) are reported. An assessment of the available thermodynamic data of gaseous and solid C a is then presented. Gibbs free energy minimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 108 publications
3
9
0
Order By: Relevance
“…Literature also exists describing the creation of fullerenes in soot by hot-® lament chemical vapour deposition (CVD) techniques during diamond production, although in contrast to our work the substrate temperature was reported to be at least 850 ë C, with the precursor gases including a large fraction of hydrogen (Chow et al 1995). Interestingly, another detailed study has concluded that rf-PECVD is not a suitable method for producing C 60 thin ® lms ( Rocabois et al 1996).…”
Section: Please Scroll Down For Articlementioning
confidence: 68%
“…Literature also exists describing the creation of fullerenes in soot by hot-® lament chemical vapour deposition (CVD) techniques during diamond production, although in contrast to our work the substrate temperature was reported to be at least 850 ë C, with the precursor gases including a large fraction of hydrogen (Chow et al 1995). Interestingly, another detailed study has concluded that rf-PECVD is not a suitable method for producing C 60 thin ® lms ( Rocabois et al 1996).…”
Section: Please Scroll Down For Articlementioning
confidence: 68%
“…The constitution of a coherent data set for gaseous C 60 and C 70 is investigated in the first part. Although only homogeneous (gas-phase) calculations are presented in this study, this first part is completed by also introducing a thermodynamic assessment of solid C 70 together with data on solid C 60 as proposed by Rocabois et al 24 The aim is to propose the first complete thermodynamic description of the two most abundant fullerenes in both gaseous and condensed forms. In the second part, thermodynamic calculations are performed in order to explore the overall yield of C 60 and of C 70 , and their relative abundance in the gas phase for commonly adopted processing conditions.…”
Section: And References Therein)mentioning
confidence: 99%
“…Fullerenes have, in addition, been produced by pyrolysis of cyclopentadienide metal complexes (ferrocene, nickelocene, cyclopentadienyl-cobalt dicarbonyl, lithium cyclopentadienide). 14 The combustion route has been extensively reviewed by Howard et al 4 More recently chemical routes for the production of C 60 with an emphasis on thin films for microelectronic applications have been reviewed by Rocabois et al 24 This review pointed out that fullerene-containing films are currently made by a batch process, which consists of first producing the fullerene, purifying it, and then finally depositing it by different evaporation techniques. Although this way of producting C 60 layers has given promising results, a direct and continuous process of deposition would be less time consuming and/or less expensive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a promising approach, CVD has been used to prepare high‐quality carbon materials including carbon nanotubes, C 60 , and diamond . More recently, Chen et al prepared 3DGNs by CVD with NF as the template .…”
Section: Introductionmentioning
confidence: 99%